Pulsed Dye Laser for Port Wine Stains in 974 Children: A 20-Year Study in China - Xiu B; Xu Z; Xu Z; Zhang B; Wei L; Ma L (Clinical, Cosmetic and Investigational Dermatology)
Bingyu Xiu, Zhe Xu, Zigang Xu, Bin Zhang, Li Wei, Lin Ma Department of Dermatology, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of ChinaCorrespondence: Lin Ma; Li Wei, Department of Dermatology, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China, Tel +86 10 59616884, Email bch_maleen@aliyun.com; bellewli@sina.comImportance: Port-wine stain (PWS) is a congenital vascular condition involving dilation of skin capillaries and venules, significantly affecting patients’ physical and mental health. Pulsed dye laser (PDL) is widely used for PWS treatment; however, large-scale data on pediatric cases remain limited. This retrospective study aims to investigate the efficacy of laser treatment and its related factors in a large sample.Objective: To assess the clinical efficacy and adverse reactions of 595nm PDL for treating pediatric PWS and to identify factors influencing treatment outcomes.Methods: This retrospective study included 974 pediatric patients with PWS treated at Beijing Children’s Hospital from 2003 to 2021. Inclusion criteria required patients to be under 18, with solitary PWS and Fitzpatrick skin types II–IV. Treatment efficacy was evaluated using standardized photographs taken before and after treatment, with outcomes categorized by Achauer’s clearance criteria. Ridit analysis assessed the impact of variables such as gender, age, lesion location, and treatment frequency on outcomes.Results: The overall efficacy rate was 65.3%, higher in females (69.7%) than males (59.7%). Adolescents had the highest efficacy (100%) due to better compliance. Limb lesions responded best (87.5%), followed by neck (75.0%), trunk (66.7%), and head/face (63.0%). Smaller lesions (≤ 3 cm²) achieved 76.8% efficacy. Efficacy rose with sessions, reaching 84.0% after three. The mandibular branch (V3) had the highest trigeminal efficacy (68.5%). Adverse reactions (4.31%) included pigmentation changes (2.87%), hypopigmentation (1.03%), and minimal scarring (0.41%).Conclusion: The efficacy of 595nm PDL for treating PWS in children is influenced by gender, age, lesion location, size, and the number of treatment sessions. PDL is an effective treatment for pediatric PWS with minimal adverse reactions.Keywords: port-wine stain, 595nm pulsed dye laser, children